Formation of Primary School Children’s Speech Competence: War Vocabulary - Derkachova, Olga; Dybovska, Olesia (Journal of Vasyl Stefanyk Precarpathian National University, 2024)
The article highlights the peculiarities of the formation of primary school children’s speech competence during the war. The war vocabulary is analyzed. It is noted that speech competence is an important component of the formation of a primary school children language identity. The attention is focused on the fact that children use military and war lexis actively, and this is not surprising, as Ukrainian children are children of war. It is proved that the formation of children's speech competence in the conditions of war is possible with careful work on the oral and written speech of schoolchildren. The peculiarities of the use of war words by primary schoolchildren in their oral and written speech was analyzed as well as war vocabulary in drawings and letters to the Ukrainian soldiers. The questionnaire revealed what words such children use in everyday communication, whether they know the meaning of these words, including new ones, and identified the most commonly used items and phrases. Most of them refer to Ukrainian soldiers, weapons, and equipment. The letters express appreciation and admiration for Ukrainian heroes and produce prayers for their safe lives. The children’s written speech is more controlled and restrained than their oral speech, but at the same time keeps childish emotions and spontaneity. In their oral speech, they use phrases familiar to all Ukrainians that have arisen since the beginning of the full-scale invasion, they know many songs, mostly “adult”, written during the years of 2022-23. These lexis and phraseology are a part of the vocabulary of a modern primary schoolchild and define the peculiarities of the speech of the children of war.